Self‐Standing Fluorine‐Free Anode Microporous Layers Enabling Improved Hot and Dry Operation of Fully Hydrocarbon Proton‐Exchange Membrane Fuel Cells - Koray Yildirim; Florian Lombeck; Severin Vierrath; Matthias Breitwieser (Advanced Energy & Sustainability Research)
Optimizing fuel cells for hot and dry conditions is crucial for heavy‐duty vehicle applications. This study focuses on enhancing gas diffusion layers (GDLs) to improve water management and performance of hydrocarbon (HC) catalyst‐coated membranes (CCMs). Thirty‐micrometer thin, self‐standing, and fluorine‐free microporous layers (SS‐MPLs) for fuel cell anodes using carbon black, graphite, and acrylic binder are developed. The impact of carbon black and binder quantities in SS‐MPL compositions on morphology, surface wetting, permeability, electrical resistance, and electrochemical performance is investigated. The SS‐MPLs demonstrate more homogeneous morphology and ≈10 times lower permeability compared to commercial references. Increasing carbon black in the SS‐MPLs reduces permeability by a factor of ≈5. Contact angle measurements indicate a hydrophilic nature for all SS‐MPLs, which is beneficial for water retention in hot and dry conditions. Optimal composition of 30% binder and 25% carbon black for the MPL, enabled a 41% higher current density (1243 mA cm−2) compared to the commercial anode GDL reference H14Cx653 (881 mA cm−2) at 0.65 V in 105 °C under 35 and 60% relative humidity at the anode and cathode. These results highlight the importance of GDLs in future membrane electrode assembly designs, particularly for HC‐based CCMs, which are more sensitive to humidity.